Estimation of a runner's speed based on chest-belt integrated inertial sensors - Vetter, R.; Onillon, E.; Bertsch, M. (The Engineering of sport 7, Volume 1, 2008)
In long distance running, real time monitoring and performance optimization has been recently rendered possible through the commercialization of a large variety of running Computers. Generally, such Computers simultaneously monitor several parameters such as heart rate, running speed, stride frequency and stride length. More precisely, stride and speed information is obtained using foot located inertial sensors. Unfortunately, due to its leg extremity location, the foot inertial sensor presents some disadvantages: it may be perceived as cumbersome; it requires supplementary telecommunication facilities as well as local power supply; it may increase a runner's energy expenditure even though it weights only a few tens of grams.